Virtual Reality and Ergonomics: Making the Immersive Experience - Ferreira Cavalcanti, Janaina; Armando Duarte, Fernanda Carolina [UNESP]; Figueiredo Ayabe, Rodrigo Crissiuma [UNESP]; Barbosa da Silva, Anderson Goncalves [UNESP]; Soares, M. M.; Rosenzweig, E.; Marcus, A. (Springer, 2021)
The hardware requirements of Virtual Reality (VR) environments are more affordable each day. Users can be immersed in virtual environments by different technologies but the most affordable immersive technology with enough feature is Head-mounted display (HMD), a visual display that is more or less rigidly attached to the head. Devices like HTC Vive and Oculus Rift allow creating VR experience with reduced budget and high levels of interaction. The human experience is a multisensory process, which shifts according to changes in perception and individual experiences. Ergonomics emerges as an indispensable discipline for human interaction with the new technologies providing high usability (efficiency, learnability and satisfaction), proper functionality (easy navigation, easy interface condition) and achieving the most varied possible ends of them. To supply which aspects provides a better experience, recent research addressing technical and structural issues of technological devices will be considered, taking into account the immersion variables and the user's comfort. It will be shown that since of the hand-held stereoscope by David Brewster among of the years, there is an incessant search for the creation of what is not presented, sharpening our imagination, capturing our attention and providing new interactions. Also, since the Renaissance technology has become an essential element in the perception of the gazer thanks to the development of optical devices and techniques for representing the perspective. This synthesis of current research will be helpful to VR Researchers, developers, designers, entrepreneurs, managers, marketers and users to select the appropriate features and hardware for each VR experience abstract should summarize the contents of the paper in short terms, i.e. 150-250 words.
Keywords: Virtual reality; Immersive design; Virtual reality devices; Ergonomics; Human-computer interaction